Lithiated ternary compounds for neutron detectors: material production and device characterization of lithium zinc phosphide and lithium zinc arsenide - Montag, Benjamin W. (Kansas State University, 2015)
There is a need for compact, rugged neutron detectors for a variety of applications including national security and oil well logging. A solid form neutron detector would have a higher efficiency than present day gas filled ³He and ¹⁰BF ₃ detectors, which are standards currently used in the industry today. A sub-branch of the III-V semiconductors is the filled tetrahedral compounds, known as Nowotny-Juza compounds (A[superscript I]B[superscript II]C[superscript V]). These materials are desirable for their cubic crystal structure and semiconducting electrical properties. Originally studied for photonic applications, Nowotny-Juza compounds have not been fully developed and characterized. Nowotny-Juza compounds are being studied as neutron detection materials here, and the following work is a study of LiZnP and LiZnAs material development and device characterization. Precursor binaries and ternary materials of LiZnAs and LiZnP were synthesized in-house in vacuum sealed quartz ampoules with a crucible lining. Synthesized powders were characterized by x-ray diffraction, where lattice constants of 5.751 ± .001 Å and 5.939 ± .002 Å for LiZnP and LiZnAs, respectively, were determined. A static vacuum sublimation in quartz was performed to help purify the synthesized ternary material. The resulting material from the sublimation process showed characteristics of a higher purity ternary compound. Bulk crystalline samples were grown from the purified material. Ingots up to 9.0 mm in diameter and 13.0 mm in length were harvested. Individual samples were characterized for crystallinity on a Bruker AXS Inc. D2 CRYSO, energy dispersive x-ray diffractometer, and a Bruker AXS D8 DISCOVER, high-resolution x-ray diffractometer with a 0.004° beam divergence. High-resolution XRD measurements indicated reasonable out-of-plane and in-plane ordering of LiZnP and LiZnAs crystals. Devices were fabricated from the LiZnP and LiZnAs crystals. Resistivity of devices were determined within the range of 10⁶ – 10¹¹ Ω cm. Charge carrier mobility and mean free drift time products were characterized for electrons at 8.0 x 10⁻⁴ cm² V⁻¹ ± 4.8% and 9.1 x 10⁻⁴ cm² V⁻¹ ± 4.4% for LiZnP and LiZnAs respectively. Sensitivity to 337 nm laser light (3.68 eV photons) was observed, where an absorption coefficient of 0.147 mm⁻¹ was determined for LiZnAs devices. Thermal neutron sensitivity was evaluated with unpurified and purified LiZnP and LiZnAs devices. Sensitivity was observed, however material quality and crystalline quality significantly hindered device performance.
Keywords: Radiation detector; X-ray diffraction; Material synthesis; Crystal growth; High temperature; Aerospace Engineering (0538); Materials Science (0794); Nuclear Engineering (0552); Nuclear Physics (0756)